Visual Acuity of Patients after Neodymium:Yttrium-Aluminium-Garnet Laser at Cicendo Eye Hospital in 2013-2014 - Yie, Lee Pei; Budiman, Budiman; Prajitno, Ihrul Prianza (Althea Medical Journal, 2016)
Background: Indonesia ranks the second highest in blindness worldwide. One of the factors that may cause blindness is posterior capsule opacification (PCO), a secondary cataract that developed after cataract surgery. PCO eventually leads to visual impairment. The common management for PCO is neodymium:yttrium-aluminium-garnet (Nd:YAG) laser posterior capsulotomy. It is an effective, non-invasive, and painless procedure. The aim of this study was to describe the visual acuity of PCO patients after Nd: YAG laser posterior capsulotomy.Methods: A descriptive study was conducted based on simple randomized secondary data from Cicendo Eye Hospital, Bandung from January 2013 to August 2014.Results: Out of 102 patients, 53 patients (51.96%) were male and 49 (48.04%) were females. The male to female ratio was 1:1. The maximum number of patients was at age group of 60â69 years (33.33%). Sixtyânine patients (67.65%) presented mild or no visual impairment uncorrected visual acuity (UCVA) post-laser. Eighty-nine patients (87.25%) presented mild or no visual impairment best-corrected visual acuity (BCVA) post-laser. Generally, 94 patients (92.16%) showed improvement of visual acuity after Nd:YAG laser posterior capsulotomy. Three patients (2.49%) were suffering from blindness UCVA post-laser and 1 patient (0.98%) falls at blindness BCVA post-laser respectively.Conclusions: Improvement of visual acuity is achieved after Nd:YAG laser posterior capsulotomy in PCO patients. [AMJ.2016;3(1):99â102]DOI:Â 10.15850/amj.v3n1.719